KONSENTRASI AMONIAK, NITRAT DAN FOSFAT DI PERAIRAN DISTRIK DEPAPRE, KABUPATEN JAYAPURA - Baigo Hamuna; Rosye H. R. Tanjung; Suwito Suwito; Hendra Kurniawan Maury (EnviroScienteae, 2018)
The determination of water quality status was needed as a reference to monitor water pollution. The purpose of this study was to determine the concentration of ammonia, nitrate, and phosphate in Depapre waters, Jayapura Regency. Sampling was carried out in October 2017 across five research stations, then the results were compared with water quality standards based on KEPMEN-LH No. 51 Tahun 2004 for marine biotas. Based on the analysis of water quality in Depapre waters obtained the following results are the ammonia content ranges from 0.8 to 11.6 mg/L, the content of nitrate ranged from 0.009 to 0.54 mg/L, and the phosphate content ranged from 0.016 to 1.19 mg/L. These results indicate that the ammonia, nitrate and phosphate concentration in Depapre Waters have exceeded the water quality standard. The concentration of ammonia, nitrate, and phosphate is high enough and endanger the lives of marine biotas.